Preliminary Evaluation of Antidiarrheal, Hypoglycemic, Analgesic and Antibacterial Activities of Diospyros blancoi Barks and Leaves (Bangladesh Pharmaceutical Journal, 2025)
Diospyros blancoi, a member of the Ebenaceae family, has been broadly used in traditional medicine. This study was carried out to assess the antidiarrheal, hypoglycemic, analgesic and antibacterial activities of methanol extract of barks and leaves of D. blancoi. The methanolic extracts of D. blancoi barks and leaves at a dose of 400 mg/kg inhibited 29.22% (p < 0.01) and 19.13% (p < 0.05) diarrheal defecation, respectively. The methanolic extract of barks did not show significant analgesic activity in the acetic acid-induced writhing method. However, the extract of leaves exhibited notable activity with 40.88% (p < 0.001) pain-mediated writhing inhibitory effect. Both the extracts of barks and leaves demonstrated very mild antibacterial activity. In the hypoglycemic activity evaluation, both the extracts of barks and leaves significantly reduced the plasma glucose level in the experimental mice at the 2nd and 3rd hours of sample administration. The study outcomes validated the traditional applications of D. blancoi leaves and barks, as well as indicated potential medicinal benefits. More comprehensive phytochemical research on D. blancoi barks and leaves would be desirable to find bioactive substances.Bangladesh Pharmaceutical Journal 28(1): 49-55, 2025 (January)